PEMETAAN SPASIAL RISIKO DAN ESTIMASI TOTAL KERUGIAN EKONOMI KEBAKARAN LAHAN GAMBUT DI PROVINSI RIAU, INDONESIA - Justica, Alma
Peatlands in Riau Province play a crucial role in carbon storage and climate regulation in Indonesia. However, they face recurring fire threats due to factors such as deforestation and human activities. To address this issue, a study was conducted to develop spatial risk mapping of peatland fires, particularly in Riau Province, Indonesia, and to estimate the total economic losses resulting from these fires by considering probabilistic elements derived from a logistic regression model. The study utilized active fire/hotspot data from NASA FIRMS, water table height data from PRIMS Gambut, and topographic map data from BIG. A logistic regression model was applied to predict the likelihood of fire occurrence based on variables such as water table height, nearest distance to human activities, and vegetation type. The results of the study indicated that the developed logistic regression model had an accuracy of 63.74% in predicting peatland fires. Significant variables included water table height, nearest distance to human activities, and the presence of fields, forests, and shrubs. The resulting spatial fire risk map indicated five risk levels: low, low-high, moderate, moderate-high, and high. Based on the study findings, of all the peatlands in Riau Province, 13.01% were identified as low-risk, 29.05% as low-high risk, 12.38% as moderate risk, 31.64% as moderate-high risk, and 13.93% as high risk. The estimated economic loss due to peatland fires in Riau Province reached IDR 17.2 trillion (or equivalent to USD 1 billion) based on Monte Carlo simulation results. This encompasses losses in various sectors including plantations, forestry, mangrove forests, biodiversity, and carbon emissions, emphasizing the multifaceted consequences of peatland fires.